2019
DOI: 10.3390/met9111234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tool Edge Geometry on Chip Segmentation and Exit Burr: A Finite Element Approach

Abstract: The effects of different tool edge geometries (hone and chamfer (T-land)) on quantitative measurement of end (exit) burr and chip segmentation (frequency and degree) in machining of AA2024-T351 are presented in this work. The finite element (FE) approach is adopted to perform cutting simulations for various combinations of cutting speed, feed, and tool edge geometries. Results show an increasing trend in degree of chip segmentation and end burr as hone edge tool radius or chamfer tool geometry macro parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This is due to the coolant pressure and enhancement of fluid delivery through channels which leads to a reduction of the chip-tool contact length while also tends to break the chip. To quantify the chip geometry, the degree of chip segmentation (G) is defined as (H max -H min )/H max , where H max and H min are the maximum and minimum chip thickness respectively [44]. Under coolant conditions, the flat insert produced a segmentation of G = 0.500, only to see a 10.9 % reduction due to the microchannels (G = 0.446), which is line with the lower friction coefficient that this insert produces (refer to Table 2).…”
Section: The Role Of the Microchannels Upon Chip Morphologymentioning
confidence: 99%
“…This is due to the coolant pressure and enhancement of fluid delivery through channels which leads to a reduction of the chip-tool contact length while also tends to break the chip. To quantify the chip geometry, the degree of chip segmentation (G) is defined as (H max -H min )/H max , where H max and H min are the maximum and minimum chip thickness respectively [44]. Under coolant conditions, the flat insert produced a segmentation of G = 0.500, only to see a 10.9 % reduction due to the microchannels (G = 0.446), which is line with the lower friction coefficient that this insert produces (refer to Table 2).…”
Section: The Role Of the Microchannels Upon Chip Morphologymentioning
confidence: 99%
“…The main outcome of the study was to discover that chip segmentation intensity and frequency are sensitive to fracture initiation strain models. Additionally, using the finite element method, but now based on an AA2024 T351 aluminum alloy, Muhammad Asad [36] studied the influence of the tool's geometry, namely hone and chamfer, on chip segmentation and burr formation. The study demonstrated an increasing trend in the degree of chip segmentation and end burr as hone edge tool radius or chamfer tool geometry macro parameters concerning chamfer length and angle increased.…”
Section: Contributionsmentioning
confidence: 99%
“…The edge preparation had a significant effect on the cutting forces [18]. The influence of different cutting edge microgeometry (rounding and chamfer) on the quantitative measurement of end burr and chip segmentation in the machining of AA2024-T351 was presented in research of Asad [19]. The effect of the tool material and edge preparation had the greatest percentage contribution to flank wear [20].…”
Section: Introductionmentioning
confidence: 99%